De (re)conto e (des)encanto: uma leitura de Fita verde no cabelo - Elvya Ribeiro Pereira (Estudos de Literatura Brasileira Contemporânea)
Fita verde no cabelo: nova velha história (Green ribbon in her hair: new old story), tale of Guimarães Rosa, presents a reading of Chapeuzinho Vermelho (Little Red Rid- ing Hood). As the sub-title indicates - new old story - Rosa's narrative reframes traditional versions of Little Red Riding Hood, projecting the story amid the be-wilderment of the modern world, deconstructing certainties, shifting fantasies. Based on reflection about oral tradition, narrative and memory, denial of the contemporary world experience, we aim to show how the tale of Guimarães questions the protagonist’s trajectory, Green-Ribbon, unfolds in a symbiosis with speechfact of a narrator plotting the destiny of this legendary girl, now in a dramatic situation, evoking gestures and archetypes that escape through the spaces of her disenchanted consciousness. The old time fairy fantasy, required by her language being and her universe ontologically situated on the very plot of the tale, about the reflux of a time of crisis, in which confrontation with loneliness is a face of death.